Do multinational firms respond to personal dividend income tax rates? - M. Jonathan C. Eklund (Empirical Economics, 2021)
This study examines the effect of investor-level income taxes on profit repatriation and dividend payout policies of multinational firms. The empirical estimations include two million firm-year observations in 130 countries. By augmenting the Lintner model of dividend payments, I employ parametric as well as semiparametric techniques to provide evidence that income taxes on dividends neither alter dividend payments to investors nor within-firm dividend payments. These results remain robust to a wide range of alternative specifications.
Keywords: 330; Dividend income taxes; Dividend payments; Lintner model; Semiparametric estimation; Multinational firms